Cellulose and TiO2–ZrO2 Nanocomposite as a Catalyst for Glucose Conversion to 5-EMF - Fitriyah Wulan Dini; Helmiyati Helmiyati; Yuni K. Krisnandi (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
This work demonstrated the use of green material catalysts, produced from Sengon sawdust waste, to obtain nanocellulose biopolymers. The green material catalysts were utilized as catalysts support of TiO2−ZrO2 binary oxide in the form of nanocomposite materials with superior synergistic properties. The isolation of nanocellulose was achieved using a hydrolysis method with a yield of 63.40%. The TiO2 and ZrO2 nanoparticles have average particle sizes of around 25 and 15 nm, respectively, and the binary oxides of TiO2–ZrO2 pretained an average particle size of 30 nm were used. Furthermore, the nanocellulose combined with the TiO2−ZrO2 binary oxide had formed a cellulose/TiO2−ZrO2 nanocomposite with an average particle size of 30 nm. This indicates that the supporting nanocellulose can stabilize the nanoparticles and avoid aggregation. Moreover, the nanocomposites can be used as a catalyst for the conversion of glucose to 5-ethoxymethylfurfural (5-EMF). The catalytic activity increased with the nanoparticle effect obtained ZrO2, TiO2, TiO2-ZrO2, and cellulose and TiO2-ZrO2 nanocomposite, in 15.50%, 20.20%, 35.20%, and 45.50% yields, respectively. The best yield of 5-EMF was 45.50%, with reaction conditions of 1:1 TiO2–ZrO2 ratio, 4 h reaction time, and 160 °C reaction temperature. The use of nanocellulose biopolymer generated from Sengon sawdust waste in Indonesia provides a promising catalyst support material as an alternative green catalyst. In addition, the glucose carbohydrates can be converted to biofuel feedstocks in the development of a renewable alternative energy. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).